Books in Brief (The Biblical archaeology review, 1979)
Philo of Alexandria Samuel Sandmel (Oxford University Press, 1979) 104 pp. $12.95 In the early first century A.D. in Alexandria, as in the rest of the Greco-Roman world, Hellenism and Judaism had blended together; Philo Judaeus embodied this mixture.